Transformation of BRIS, BNIS, and BSM into BSI : A Comparative Analysis of Financial Performance Using CAR, NPF, FDR, and ROA - Ahmad Masy'aril Fuadi; Aufar Fadlul Hady; Khusnul Fikriyah (Jurnal Maps (Manajemen Perbankan Syariah), 2026)
The transformation of three state-owned Islamic banks BRIS, BNIS, and BSM into BSI represents a strategic initiative by the government to strengthen the national Islamic banking industry. This study conducts an in-depth analysis of the financial performance  differences of the three banks before and after the merger during the 2016–2024 period, using the indicators CAR, NPF, FDR, and ROA. A quantitative method with a descriptive approach and a Paired Sample T-Test was employed based on published financial statements. The findings indicate that, on average, financial performance improved after the merger. Significant differences were observed in the FDR and ROA ratios, both of which increased post-merger, whereas CAR and NPF Did not exhibit substantial changes. These analysis implies that the merger positively contributed to enhancing financing efficiency and profitability, although it has not yet had a substantial impact on capital adequacy or financing quality. This research is anticipated to act as a guide for government decision-making, regulators, and industry practitioners in assessing the effectiveness of consolidation efforts within Indonesia’s Islamic banking sector.